The American Historical Collection Library description and analysis of use - Sabalones, Arcadia C.; Hidalgo, Namnama P.; Lewis, E. Gleeck Jr. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1982)
This study described the American Historical Collection Library - its history, the various collections and resources comprising it, and the library services - and analyzed in-depth the use made of these resources by scholars and other users.
The descriptive method of research was used. Documentary analysis and user survey utilized personal observations, interviews and questionnaire as data gathering instruments. With the questionnaire a letter was enclosed requesting an evaluation of resources used on each subject researched on especially by scholars and authors, institutions and organizations here and abroad.
The respondents to the user questionnaire were identified from the Library's user logbook and from acknowledgements in published materials written by scholars who used the AHC Library. Personal interviews were conducted with people who were personally connected with the Library's founding, organization and management. Letters were also sent to donors / benefactors and owners of purchased collections that are now in the Library. Primary source materials which were available and have been used included the Minutes of the American Historical Committee Meetings 1950-1981; the annual reports of the Chairman of the American Historical Committee; reports of the librarian and other papers.
The greatest strength of the AHC Library as perceived by the respondents is anchored in its almost complete collection on the American period in the Philippines: periodicals, magazines, newspapers, journals, photographs, ephemera, pre-war and wartime materials. Primary sources and government documents and publications, both of the Philippine and United States governments, contribute to this.
he over-all impression of the users is that the physical location, facilities and working conditions - the ambience - is not found in other libraries. Inadequacies of the library include 1) microfilm incapability, 2) lack of publicity, 3) gaps in the collection, and 4) inadequacy of the Library's quarters.
On the basis of the findings summarized above, the following conclusions were formulated: The AHC Library is a collection of the most important primary and secondary sources in Philippine history during the period 1898-1946. It also has significant materials before and beyond this period. Its specialization, physical location, services and library staff, have all contributed to make the AHC Library an important stop for scholars and academicians, who have been thoroughly satisfied in their use of the Library.
To achieve the purposes of this study, the researcher made the following recommendations: As a special library, the AHC Library does not have to do everything but it has to concentrate on doing what it does very well. The focus on the American period should be really re-enforced by acquiring relevant new publications and identifying gaps in the collection for long-term retrospective acquisition of photocopies. ; Acquiring microfilm copies of papers of American officials who served in the Philippines would be a valuable addition to the Collection. ; There should be concerted and augmented efforts to advertise the AHC Library. Once the publicity program is off the ground, the Library has lots of attraction and positive features that would make users who once used the Library to return with pleasure and expectancy. ; The existence and use of the materials at the American Historical Collection Library will help supply that long-felt need for sources about our national history and make them available and accessible to Filipino scholars who are not able to go abroad.
Mimeographed.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: American Historical Collection Library; Libraries--Evaluation.